2020
DOI: 10.3390/nu12102996
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Gut Microbiota are Associated with Hypertension, Hyperlipidemia, and Type 2 Diabetes Mellitus in Japanese Subjects

Abstract: The human gut microbiota is involved in host health and disease development. Therefore, lifestyle-related diseases such as hypertension (HT), hyperlipidemia (HL), and type 2 diabetes mellitus (T2D) may alter the composition of gut microbiota. Here, we investigated gut microbiota changes related to these diseases and their coexistence. This study involved 239 Japanese subjects, including healthy controls (HC). The fecal microbiota was analyzed through the isolation of bacterial genomic DNA obtained from fecal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
1
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 31 publications
3
61
1
2
Order By: Relevance
“…Furthermore, Lactobacillaceae composition was lower in the BC and positive-C groups than in the control group, but Akkermansia muciniphila contents were much higher in the BC group than the control. Intake of anthocyanin-rich foods, such as blackcurrants and blackberries, enriches Akkermansia muciniphila , which is consistent with our findings [ 51 , 52 ]. Fecal Bacteroidetes levels are significantly decreased in T2DM patients, similar to the findings of the present study [ 53 ].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, Lactobacillaceae composition was lower in the BC and positive-C groups than in the control group, but Akkermansia muciniphila contents were much higher in the BC group than the control. Intake of anthocyanin-rich foods, such as blackcurrants and blackberries, enriches Akkermansia muciniphila , which is consistent with our findings [ 51 , 52 ]. Fecal Bacteroidetes levels are significantly decreased in T2DM patients, similar to the findings of the present study [ 53 ].…”
Section: Discussionsupporting
confidence: 92%
“…Most studies (11/13 studies) showed that significant differences between hypertension group and control group were detected (18-20, 22, 23, 26, 27, 30-33). Two studies reported that no significant differences were seen (29,34).…”
Section: Change Of Gut Microbiota Diversity In Hypertensionmentioning
confidence: 99%
“…The characteristics of included studies were summarized in Table 1. Most of them were published in year 2019 (6/17 studies) (23)(24)(25)(26)(27)(28) and year 2020 (6/17 studies) (29)(30)(31)(32)(33)(34); in terms of geographical region, most of these researches were conducted in China (9/17 studies) (18-21, 23, 25, 27, 28, 30) and the US (3/15 studies) (22,27,31), which are two countries with heavy disease burden of hypertension. For study design, most studies enrolled a group of fecal samples from hypertension cases and a group of fecal samples from healthy controls with normal blood pressure; the major exploration was based on comparison between the two groups; three studies (18,20,24) also enrolled subjects of pre-hypertension or in borderline status.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…A recent study stated that COVID-19-positive older people presenting with chronic medical conditions such as high blood pressure, diabetes, and obesity are at a higher risk for hospitalization and mortality than older people without these chronic conditions [ 75 ]. These latter are associated with numerous changes in the structure of the gut microbiota of humans [ 76 79 ]. Interestingly, Gu et al .…”
Section: Discussionmentioning
confidence: 99%